PEMANCAR TELEVISI VHF MENGATASI BLANK SPOT DI TULAKAN PACITAN - Heri Wijayanto (MEDIA ELEKTRIKA, 2009)
Television program becomes a daily needs for most people, we can find as the television sets in everyhouse. Even more on in rural area. The program is more and more interesting and news presented lively.And television is a vital for the people.But the blank spot (electromagnetic coverage area wave), it is very hard to get the program. As it isgeographical area that does not work for UHF television broadcast relay whether private or state program.If the blank spot area wants to get the program they have to spend a lot costs on trying to afford the satellitedish. It is not easy to afford to cost of this device.It is the problem of Bubagan people in Tulakan district, Pacitan regency. They do not have televisionsignal for UHF. If they wish to get it, they have to spend a lot of cost in enjoying Television program. Asthey have to buy satellite dish. In this area most people do not have television sets